SISTEM PERSEDIAAN - Wisky, Irzal Arief (LPPM UPI YPTK PADANG, 2019)
The purpose of this research is to produce applications that can provide information about inventory, because this is very important in the world of organizations engaged in marketing and selling goods. So from that the authors conducted research on hasanah collection, implementation is applied to determine improving the ability of the inventory system in scheduling and selling processes. For this reason, a computerized system was built so as to minimize the calculation error to determine the amount of ending inventory in hasanah collection.